Exploring the Effect of Selenidation Time on the Ni-Doped Cu2ZnSn(S,Se)4 Solar Cell - Fancong Zeng; Jingshu Wang; Meiling Ma; Na Zhao; Tianyue Wang; Guangbo Chen; Bin Yao; Yingrui Sui (Nanomaterials, 2022)
The Cu2Ni0.05Zn0.95Sn(S,Se)4 (CNZTSSe) films were synthesized by sol-gel combined with selenidation treatment. To further enhance the crystal quality of the film, the selenidation conditions were optimized, and the effects of selenidation time on the properties of the CNZTSSe films and devices were systematically studied. The results show that the crystallinity of the films increased remarkably with the increase of selenidation time. Under the optimum selenidation time of 15 min, smooth and dense films were obtained. Through the analysis of EDS results, it is found that Se occupies more S positions with the increase of selenidation time, which decreases the band gap of the film from 1.14 eV to 1.0 eV. In addition, the formation of Zn-related defects is effectively suppressed by Ni doping to enhance the open circuit voltage (Voc) of the CNZTSSe solar cells. When the selenidation time is 15 min, the CNZTSSe film has the highest carrier concentration of 1.68 × 1016 cm−3, and the best efficiency of the device prepared based on the film as the absorption layer is 5.0%, and the Voc is 337 mV.